TRANSFORMING LEARNING AT IJEN GEOPARK BONDOWOSO: A DEEP LEARNING APPROACH INTEGRATING SCIENCE, ECOLOGY, AND CULTURE IN THE MERDEKA CURRICULUM: Transformasi Pembelajaran Ijen Geopark Bondowoso: Pendekatan Deep learning yang Menghubungkan Sains, Ekologi, dan Budaya dalam Kurikulum Merdeka - Rahman Abidin; Gandung Wirawan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to examine the use of Ijen Geopark in Bondowoso, East Java as a learning space that supports deep learning within the implementation of the Merdeka Curriculum. Despite its strong potential, the educational use of geoparks is often limited, fragmented, and still dominated by tourism and conservation perspectives, with few studies explaining how geoparks function pedagogically to facilitate deep learning in school contexts. The geopark, consisting of geosites, biosites, and cultural sites, is therefore explored as a living laboratory that integrates science, ecology, and culture. This research employed a qualitative case study approach. Data were collected through field and classroom observations, in-depth interviews with teachers, students, and geopark managers, as well as document analysis, and were analyzed thematically through coding and categorization processes. The findings show that geopark-based learning strengthens students’ critical thinking, ecological awareness, collaboration, and meaningful conceptual understanding. In addition, learning activities encourage interdisciplinary connections and authentic learning experiences relevant to the Merdeka Curriculum. However, several challenges were identified, including unequal teacher readiness, limited facilities at some learning sites, and logistical constraints. In conclusion, Ijen Geopark has strong potential to function as a sustainable living laboratory that supports deep learning and interdisciplinary education. This study contributes to the development of a practical model of geopark-based deep learning and emphasizes the need for stronger institutional, pedagogical, and infrastructural support to optimize its implementation.